Effects of feeding low fishmeal diets with increasing soybean meal levels on growth, gut histology and plasma biochemistry of sea bass. (17th October 2017) - Bonvini, E.; Bonaldo, A.; Mandrioli, L.; Sirri, R.; Dondi, F.; Bianco, C.; Fontanillas, R.; Mongile, F.; Gatta, P. P.; Parma, L.
Abstract : The aquaculture industry depends upon the development of sustainable protein sources to replace fishmeal (FM) in aquafeeds and the products derived from soybeans are some of the most studied plant feedstuffs. A key area of investigation for continuing to improve modern aquafeeds includes the evaluation of varying proportions and combinations of plant ingredients to identify mixtures that are more efficiently utilized by the fish. This study investigated the effects of increasing soybean meal (SBM) by replacing a mix of plant ingredients in low FM (20%) diets on growth, blood biochemistry profile and gut histology on European sea bass. Five isonitrogenous and isolipidic experimental diets were formulated: four diets containing increasing SBM levels (0, 10, 20 and 30%; 0SBM, 10SBM, 20SBM and 30SBM, respectively) with a low content of FM (20%) and one control diet (0% SBM; 35% FM). Diets containing SBM brought to comparable performance and protein utilization, while 0SBM had negative impact on feed conversion rate and protein utilization. Blood parameters suggested an optimal nutritional status under all feeding treatments, even though slightly decreased values were reported at increasing dietary SBM. Histology examination did not show any changes indicative of soy-induced enteritis. We can conclude that for European sea bass: (i) different blends of plant protein did not affect feed intake despite the 20% FM dietary level; (ii) the inclusion of SBM maintains optimal growth and feed utilization in low FM diets; (iii) blood biochemistry profile showed a good nutritional status under all feeding regimes; (iv) no evidence of soy-induced enteritis was reported in any group fed low FM diets. For formulation of practical diets in on-growing of European sea bass, SBM up to 30% can be successfully incorporated into feeds containing low FM inclusion.